2004
DOI: 10.1080/00364820410002695
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination among species of the genus Sebastes in the North Atlantic by random amplified polymorphic DNA

Abstract: Johansen T, Dahle G. 2004. Discrimination among species of the genus Sebastes in the North Atlantic by random amplified polymorphic DNA. Sarsia 89:478-483. SARSIAGenetic variation among and within species of the genus Sebastes [S. viviparus, S. fasciatus, S. mentella (including deep-sea and oceanic types) and S. marinus (both ordinary and giant types)] from the North Atlantic was investigated by polymerase chain reaction (PCR)-based random amplification of polymorphic DNA (RAPD). Initial analyses were based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…DNA sequences have not been indentified, random amplified polymorphic DNA (RAPD) can be used to explore the patterns of variability, because RAPD primers recognize simple nucleotide sequences that should arise frequently in any DNA (Smith, 2005). Johansen et al (1997) and Johansen and Dahle (2004) found significant differences in allele frequencies of four RAPD primers among all samples of S. mentella from the Gulf of St Lawrence, Norway, and the Irminger Sea (oceanic and deep-sea). However, RAPDs produce results that may not be repeatable and are no longer considered to be a reliable approach for testing population-structure hypotheses.…”
Section: Nuclear Dnamentioning
confidence: 99%
“…DNA sequences have not been indentified, random amplified polymorphic DNA (RAPD) can be used to explore the patterns of variability, because RAPD primers recognize simple nucleotide sequences that should arise frequently in any DNA (Smith, 2005). Johansen et al (1997) and Johansen and Dahle (2004) found significant differences in allele frequencies of four RAPD primers among all samples of S. mentella from the Gulf of St Lawrence, Norway, and the Irminger Sea (oceanic and deep-sea). However, RAPDs produce results that may not be repeatable and are no longer considered to be a reliable approach for testing population-structure hypotheses.…”
Section: Nuclear Dnamentioning
confidence: 99%
“…Due to the difficulties with morphologically based determination of redfish species, genetic methods have been in the past mainly used for species discrimination (Nedreaas and Nævdal 1989, 1991; Sundt and Johansen 1998; Roques et al . 1999; Johansen and Dahle 2004). Nevertheless, some studies have also shown genetic differentiation within species mainly on large spatial scales.…”
Section: Mismatch Between Management and Biological Units In The Ne Amentioning
confidence: 99%
“…Since the main focus in these works has been related to variation within species and population genetics, a protocol describing procedures and methods to use for diagnostic identification of species using DNA techniques is still lacking. It can though be mentioned that Johansen and Dahle (2004) investigated this by polymerase chain reaction (PCR)-based random amplification of polymorphic DNA (RAPD). They found that only one primer, OPA20, could be used to diagnostically distinguish among species.…”
Section: Species Identificationmentioning
confidence: 99%